The Idea of On-line Education and Ttraps on the Way of its Realization - Khyzhniak, Larysa (Visnyk of V. N. Karazin Kharkiv National University. Series Sociological studies of contemporary society: methodology, theory, methods, 2019)
The author shows that the hope on modernization of education today is largely related to the introduction of on-line education. However, researchers and practitioners focus their attention primarily on its benefits, less studied are traps encountered in the expansion of this type of education. Under the traps of on-line education are understood circumstances, situations that hinder the manifestation of its advantages and does not allow fully discovering its possibilities. Conventionally the author divides such traps into legal (lack of a clear legal regulation of on-line education); economic (lack of economic resources among the participants of on-line education); social and psychological factors (lack of confidence to the quality of on-line education); informational factors (lack of information about where and how you can get this or that learning program by the technology of on-line education); bureaucratic (unnecessary restrictions in the licensing and accreditation of on-line educational programs and other bureaucratic problems); methodological (lack of specially adapted methods of organization of on-line education, and assessment and monitoring of students’ knowledge).